Lentiviral‐mediated overexpression of Akt1 reduces anoxia–reoxygenation injury in cardiomyocytes. (16th January 2014) - Du, Yanyan; Zhu, Hong; Li, Dongye; Wang, Lele; Zhang, Lin; Luo, Yuanyuan; Pan, Defeng; Huang, Manman
Abstract Activated PI3K/Akt signalling exerts a protective effect after myocardial ischemia by phosphorylating various substrates; however, the precise mechanism by which this occurs remains to be elucidated. We have constructed the recombinant lentiviral vector pLVX‐Akt1‐EGFP‐ 3FLAG (LV‐Akt1) to determine the efficiency of LV‐Akt1 infection, explore the protective role of Akt1, and investigate the possible mechanism by which Akt1 signalling acts during anoxia/reoxygenation (A/R) of cardiomyocytes in primary culture. Akt1 gene transfection increased cardiomyocyte pulsation, reduced cell mortality, and decreased the concentration of lactate dehydrogenase (LDH) in myocardial cells supernatants. Akt1 transfection increased the levels of intracellular p‐Akt, enhanced the expression of the anti‐apoptosis protein Bcl‐2, and reduced that of the apoptosis protein Bax (thereby increasing the Bcl‐2/Bax ratio), and caused some increase in hypoxia‐inducible factor1α (HIF‐1α) and vascular endothelial growth factor (VEGF) expression after A/R. The protective role of Akt1 was partly suppressed by adding a phosphoinositide 3‐kinase/Akt inhibitor (LY294002). In conclusion, LV‐Akt1 was successfully constructed and neonatal rat cardiomyocytes were transfected efficiently. Akt1 overexpression significantly reduced A/R injury in cardiomyocytes, and this could be related to its effects on various targets of the PI3K/Akt signalling pathway, such as Bcl‐2, Bax, HIF‐1α and VEGF.